A Multicenter Retrospective Observational Study to Correlate Sharir Guna Computed Through Nadi Pariksha (Pulse Diagnosis) Using Electronic Nadi (Pulse)Recording Device Nadi Tarangini with Trends and Changes in Rutus (Seasons) for a Span of One Year in - Bhale, Tejaswini S; Joshi, Aniruddha; Kulkarni, Shruti (International Research Journal of Ayurveda & Yoga, 2024)
Background: The theory of Rutucharya (seasonal regimen) is described in Ayurveda by Acharyas ( Ancient sages) according to the climatic changes (seasonal changes), its effect on Agni ( Digestive fire), Bala ( Strength), Tridosha ( Vata, Pitta, Kapha) i.e. 3 humors. Guna (Sharir Guna, properties) and finally on Body and Mind. Objectives: In a multi-centric retrospective observational study, we “empirically” studied the correlations between and validating the same with some of the sharir guna which reflects in nadi, for different Prakruti (body constitution) with rutus (seasons) as per ayurveda text described to prediction and diagnose signs and symptoms of the diseases. Materials and methods: We used Nadi Tarangini (a commercial wrist nadi recording system) to record nadi of 15,391 subjects across the north-west part of India throughout a span of one year. We further computed five pairs of guna (qualities) namely Guru - Laghu (Heavy- Light), Snigdha - Ruksha (Unctuous- Dryness), Manda- Tikshna (Blunt-Sharp), Sukshma- Sthula (Subtle-Bulky) and Mrudu - Kathina.(Soft-Hard) Results: For 15,391 subjects, we found significant correlation of the Guna flow throughout the span of 1 year captured using Nadi Tarangini, matching with the ancient texts such as, laghu guna increases from Varsha rutu, ruksha guna is high in Greeshma rutu and tikshna guna increases in Sharad rutu, correlating well with the electronic Nadi Tarangini findings. Conclusion: We emphasized the data-based evidence, for the first time and importance of sharir guna in Rutucharya and nidan of dosha avastha and vyadhi (signs and symptoms of diseases) through Nadi pariksha. It will be helpful to avoid lifestyle-oriented disorders and better diagnosis through nadi pariksha and also can be validated and used for the purpose of research among the common populations.